PRAGMATIC MEANING IN TRADITIONAL CAREMONIES: ENGLISH DESCRIPTIONS OF BATU BARA CULTURE - Fadli, Izhar; Suhadi, Jumino; Barus, Efendi; Maulana, Cecep (Universitas Putera Batam, 2025)
This study explores the pragmatic meanings embedded in the traditional ceremonies of the Batu Bara Malay community as expressed through English descriptions. These rituals are rich in cultural values and communicative intentions. However, they have rarely been examined from a linguistic perspective that focuses on language use in context. The main objective of this research is to investigate how ritual expressions such as blessings, symbolic utterances, and culturally marked instructions are conveyed in translated or interpreted English texts. Using a qualitative descriptive method grounded in speech act theory and ethno-pragmatics, data were collected from four primary sources: interviews with cultural figures (35%), ritual observations with audio-video recordings (30%), bilingual document analysis (25%), and field notes on the ceremonial context (10%). The results indicate that 67% of English translations partially retained the original communicative force, 23% showed significant meaning shifts, particularly in indirect speech acts and politeness strategies, and only 10% fully preserved the original sociocultural intentions. These findings reveal the complexity of maintaining cultural meanings in cross-linguistic communication and the potential for meaning loss during translation. This study contributes to a deeper understanding of cultural pragmatics in multilingual translation and highlights the importance of culturally sensitive translation practices. It concludes that such practices are crucial to preserving the sociocultural integrity of local traditions and promoting more effective intercultural understanding.